2024
DOI: 10.1021/acssensors.4c00137
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Opportunities for TiO2 Nanostructures in Gas Sensing

Jiahui Zhao,
Haiquan Wang,
Yahui Cai
et al.

Abstract: Chemiresistive gas sensors based on metal oxides have been widely applied in industrial monitoring, medical diagnosis, environmental pollutant detection, and food safety. To further enhance the gas sensing performance, researchers have worked to modify the structure and function of the material so that it can adapt to different gas types and environmental conditions. Among the numerous gas-sensitive materials, n-type TiO 2 semiconductors are a focus of attention for their high stability, excellent biosafety, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that the hydrogen bonds between the l / d -Phe and l / d -DOPA is crucial for the chiral recognition process, and the strength of this hydrogen bond is closely related to temperature. 32 As predicted, chiral substrates exhibited different chiral recognition phenomena at different recognition temperatures ( Fig. 4B–D ).…”
Section: Resultssupporting
confidence: 73%
“…Previous studies have shown that the hydrogen bonds between the l / d -Phe and l / d -DOPA is crucial for the chiral recognition process, and the strength of this hydrogen bond is closely related to temperature. 32 As predicted, chiral substrates exhibited different chiral recognition phenomena at different recognition temperatures ( Fig. 4B–D ).…”
Section: Resultssupporting
confidence: 73%
“…We also demonstrated the existence of ionchannels in the barrier layer of the as-prepared AAO membrane, which further broadens the application of AAO membranes . TiO 2 nanotube arrays can also be fabricated by anodic methods, and they have shown great potential in chemical sensing because of their high stability and unique photoelectric properties. Arrayed nanopores have the advantages of cost-effective, robust, and very easy to manipulate. They have been utilized in the analysis of a variety of complex samples.…”
Section: Nanopore Materialsmentioning
confidence: 79%
“…Given that building energy consumption constitutes a significant portion, 30%-40%, of total global energy usage, the utilization of smart windows incorporating EC materials has garnered increasing attention [4]. These advanced EC smart windows offer the dynamic regulation of solar radiation transmittance, achieved through their ability to selectively absorb or reflect external heat radiation and internal heat diffusion [5][6][7]. Consequently, they contribute to maintaining comfortable indoor temperatures, keeping spaces cool in summer and warm in winter [8].…”
Section: Introductionmentioning
confidence: 99%